Un-digitize sleep if you don't want nightmares - Mihai Nadin (Annals of Systems Biology - Peertechz Publications, 2020)
For the maintenance of machines and other mechanical devices, the more you can measure, the better. For the maintenance of life, meaningful data is essential. This understanding is not yet integrated in the views and practices of medicine. Digitizing the way to better sleep health [1], is a worrisome example.